(untitled) - Brunton, Richard Henry (1991)
o better example could be found of Japan's urgent need for imported technological expertise to help bring about her own industrial revolution in the last quarter of the 19th century than the Scottish civil engineer Richard Henry Brunton. This book is Brunton's own account of his eight years in Japan (1868-76) which has remained unpublished for over a hundred years. It is a work of some considerable scholastic importance - particularly the rare first-hand accounts of various technical developments taking place in Japan at that time. Also of interest are Brunton's personal observations relating to the evolving social, economic and political developments of early Meiji Japan. Brunton was originally commissioned to supervise the design and construction of the country's first lighthouse system; he subsequently went on to build the first telegraph line between Tokyo and Yokohama and built one of the Japan's first iron bridges. He also took on the role of educator and established a teacher-training school near his office in Yokohama "for mathematics and other cognate subjects".
Keywords: Civil engineering,Civil engineers; History,Biography; Japan,Scotland